Mapping of QTL and identification of candidate genes conferring spontaneous haploid genome doubling in maize (Zea mays L.). (April 2020) - Ren, Jiaojiao; A. Boerman, Nicholas; Liu, Ruixiang; Wu, Penghao; Trampe, Benjamin; Vanous, Kimberly; Frei, Ursula K.; Chen, Shaojiang; Lübberstedt, Thomas
Highlights: New QTLs related to spontaneous haploid genome doubling (SHGD) in maize were identified by selective genotyping. Candidate gene analysis within the qshgd1 region was conducted by RNA-seq. The down-regulation of the Formin-like-5 transcript which possibly plays a role in cell division, was identified. Abstract: In vivo doubled haploid (DH) technology is widely used in commercial maize ( Zea mays L.) breeding. Haploid genome doubling is a critical step in DH breeding. In this study, inbred lines GF1 (0.65), GF3(0.29), and GF5 (0) with high, moderate, and poor spontaneous haploid genome doubling (SHGD), respectively, were selected to develop mapping populations for SHGD. Three QTL, qshgd1, qshgd2, and qshgd3, related to SHGD were identified by selective genotyping. With the exception of qshgd3, the source of haploid genome doubling alleles were derived from GF1. Furthermore, RNA-Seq was conducted to identify putative candidate genes between GF1 and GF5 within the qshgd1 region. A differentially expressed formin-like protein 5 transcript was identified within the qshgd1 region.